Assessing the effect of consumer purchasing criteria for types of rice in Togo: A Choice Modeling Approach - Fiamohe, R.; Nakelse, T.; Diagne, M.; Seck, P.A. (Wiley, 2015)
This study analyses rice consumer preferences in Togo and estimates consumers' willingness to pay (WTP) for the quality attributes of locally produced rice. For that purpose, a random utility model is applied to elicit the WTP for the most important rice purchase criteria. The model is estimated using a survey of consumers from 15 prefectures in Togo. The results show that imported rice is largely preferred to local rice, especially in urban areas. Cleanness and whiteness appear to be the most preferred attributes, especially for imported rice. Togolese consumers are willing to pay a premium of up to 46% of the actual price for cleanness and 53% for whiteness in locally produced rice. Also, taste and swelling capacity play an important role in the preference for locally produced rice. The results might be useful for breeders and policy makers in the ongoing effort to improve the competitiveness of local rice in West Africa both from quality and price perspectives.